Legal Rules Against The Use Of Joint Accounts In Online Transactions - Nahdliyah, Hadziqotun; Nida , Khairun; Sastradinata, Dhevi Nayasari; Pramana, Hans Andika (Jurnal Independent, 2026)
Online transactions have encouraged the emergence of various forms of financial cooperation, including the use of joint accounts by parties who are not bound by conventional banking relationships such as families or business entities. This practice creates legal complexity, especially related to the status of fund ownership, the responsibilities of the parties, and consumer protection in the digital payment system. This study aims to analyze the legal framework that applies to the use of joint accounts in online transactions in Indonesia, as well as identify regulatory loopholes that have the potential to cause legal uncertainty. The method used is normative legal research with a statutory approach and a conceptual approach. The results of the study show that there is no specific regulation that explicitly regulates joint accounts for non-institutional online transactions. The existing arrangements are still general and scattered, causing uncertainty regarding risk sharing, proof of transaction authorization, and dispute resolution between account owners. This study recommends the need for regulatory harmonization and the establishment of specific guidelines by financial services authorities to provide legal certainty and protect parties using joint accounts in the online transaction ecosystem.